File Sharing & Copyright Infringement in Peer-to-Peer - Hasan, M. Zulkifl; Musa, Muhammad; Mujahid, Ahmad; Saifullah , Dr. Muhammad; Iqbal Baig, Junaid (Journal of Computers and Intelligent Systems, 2024)
In the past, we used a centralized system which is server-client architecture but today along with server-client peer-to-peer or P2P is widely used which is based on the decentralized system in it each client is also a server purpose of the server for all the different clients as well by analyzing various articles, research papers, and literary works. We investigate many software and technological innovations including Napster, uTorrent, BitTorrent, and Gnutella.Peer-to-peer technology might go either way in the future; perhaps the copyright legislation has made it better or worse. Peer-to-peer has an impact on the music and film industries, among others, since it makes it simple for users to distribute information that is protected by copyright. Additionally, this article considers copyright infringement from both domestic and foreign viewpoints. The article demonstrates the connection between peer-to-peer file sharing and copyright infringement in general as well as the difficulties in safeguarding owners' copyrights on a P2P network. People mistakenly assume that it is impossible to identify and track copyright violations, yet some tools and procedures may be used to identify material that is protected by copyrights.